The Impacts of Covid-19 on Unilever - Rudresh Pandey; Ajay Massand; Victor Teja Mulya; Liem Gai Sin; Vadlamudi Prudhvi Naresh; Faizah Binti Zamara; Daisy Mui Hung Kee; Siti Khadijah Binti Zamri; Nur Ain Syamira Binti Azmi; Noor Najihah Binti Mohd Hamdan; Aditi Aditi (AIBPM Publisher, 2021)
Unilever is a global consumer goods company which provides daily products such as soap and snacks. It is one of the oldest multinational companies distributing its products to more than 190 countries. During Covid-19 pandemic, the demand for products and services has greatly decreased, and Unilever has shown a great reaction towards the situation. The purpose of this study is to explore how Covid-19 affected Unilever and how Unilever improved the company welfare. The data collected from news, websites and other reviews. This study found that Unilever instant food products decreased as consumers focus on purchasing household products.